A Fourth-Order Compact Finite Difference Scheme for Solving the Time Fractional Carbon Nanotubes Model. (2nd March 2022) - Sweilam, N. H.; Khater, Khloud R.; Asker, Zafer M.; Kareem, Waleed Abdel
Abstract : In this work, we deal with unsteady magnetohydrodynamic allowed convection inflow of blood with a carbon nanotubes model; the single and multiwalled carbon nanotubes of human blood are used as a based fluid. Two numerical methods used to study this model are the weighted average finite difference method and the nonstandard compact finite difference method. The proportional Caputo hybrid operator has been used to fractionalize the proposed model. Stability analysis has been construed by a kind of John von Neumann stability analysis. Numerical results are presented in diverse graphs, which manifest that the method is successful in solving the proposed model.